Too little, too late? Sociological reflections on religious responses to climate crisis - Norgaard, Kari Marie (Dialog, 2024)
Are religious communities better advantaged to mobilize for social change than other institutions and communities and other social spaces? If so, how might they do so? What unique resources can religious communities offer to this effort? Even if there is no set formula to generate climate engagement, are there conditions we can recommend? As one of the few social spaces that might systematically compel collective moral engagement, religious communities and organizations hold the potential to play a key role in societal response. Religious teachings, leaders, and communities have provided individuals the moral conviction to do what is right and the courage to act when one is afraid, and they have offered a microcosm of social networks and social norms that supported social engagement. Not only do religious communities provide a rare space for moral vision and call to action, but in many cases religious communities have in fact mobilized significant social movement responses on other issues at both individual and community levels. In this essay, I apply a theory of socially organized denial to specific questions about climate inertia within religious communities posed in this special issue. I also unpack the question of “too little, too late,” pointing to the benefits of a suspension of doubt and engaging in ethics of responsibility in the unfolding present.